Technical Validation of Omron 705IT and A&D UA-767PlusBT Using Oscillometric Waveform Simulators. Issue 3 (July 2015) - Hoffmann-Petersen, Nikolai; Newell, Sara Rose; Brantlov, Steven; Pedersen, Erling Bjerregaard
<x xml:space="preserve">Abstract</x> Accurate blood pressure measurements are fundamental in order to achieve correct diagnosis and treatment of hypertension. This study performed a validation of the A&D UA767PlusBT and the Omron 705IT, using different oscillometric waveform simulators. The researchers first tested 30 monitors of the A&D UA767PlusBT using 2 different waveform simulators (Metron QA-1280 and BioTek BP Pump2). Second, we tested 5 previously used blood pressure monitors from A&D UA767PlusBT and Omron 705IT using a Fluke BP Pump 2L simulator, 5 monitors per manufacturer, 10 monitors in total. Three measurements were obtained per monitor, for each of the 8 simulated and preset patient conditions. Third, we tested new and unused blood pressure monitors from A&D UA767PlusBT and the Omron 705IT using a Fluke BP Pump 2L simulator; 10 monitors per model, 20 monitors in total. Six measurements were obtained per monitor, for each of the 8 simulated patient conditions. Using the Metron simulator, the A&D UA767PlusBT showed a significant deviation for systolic blood pressure (systolic/diastolic, −7.8 ± 2.9/1.5 ± 1.6 mm Hg). Using the BioTek simulator, the same systolic deviation was shown (systolic/diastolic, −9.1 ± 2.3/2.7 ± 3.2 mm Hg). Both systolic deviations exceed the specified measurement accuracy of ±3 mm Hg. Using the Fluke simulator, previously used A&D UA767PlusBT monitors showed similar deviations (systolic/diastolic, −10/2 mm Hg; range, −14 to −4/−7 to 7; P < .001/P < .001), whereas used Omron 705IT did not show deviations exceeding the specified level (systolic/diastolic, −1/2; range, −5 to 5/−5 to 5 mm Hg; P = .6/P < .001). Using the Fluke simulator, new and unused A&D UA767PlusBT monitors showed significant deviations exceeding the specified accuracy (systolic/diastolic, −4/2 mm Hg; range, −14 to 2/−6 to 8; P < .001/P < .001), whereas new and unused Omron 705IT monitors did not show deviations exceeding the specified level (systolic/diastolic 0/2.4 mm Hg; range, −5 to 10/−1 to 6; P < .001/P < .001). The A&D UA767PlusBT monitors measured systematically too low systolic blood pressure but exhibited good precision. Omron 705IT monitors showed both high accuracy and good precision for both diastolic and systolic values. The differences between monitors from these 2 manufacturers can most likely be attributed to differences in the algorithms used to estimate the blood pressure. The consequence for patients with hypertension would be an increased cardiovascular risk, if systolic blood pressure is estimated to be falsely too low.